Computer-Based Training in Math and Working Memory Improves Cognitive Skills and Academic Achievement in Primary School Children: Behavioral Results - Sánchez-Pérez, Noelia; Castillo, Alejandro; López-López, José A.; Pina, Violeta; Puga, Jorge L.; Campoy, Guillermo; González-Salinas, Carmen; Fuentes, Luis J. (Frontiers in Psychology, 2018)
Student academic achievement has been positively related to further development outcomes, such as the attainment of higher educational, employment, and socioeconomic aspirations. Among all the academic competences, mathematics has been identified as an essential skill in the field of international leadership as well as for those seeking positions in disciplines related to science, technology, and engineering. Given its positive consequences, studies have designed trainings to enhance children’s mathematical skills. Additionally, the ability to regulate and control actions and cognitions, i.e., executive functions (EF), has been associated with school success, which has resulted in a strong effort to develop EF training programs to improve students’ EF and academic achievement. The present study examined the efficacy of a school computer-based training composed of two components, namely, working memory and mathematics tasks. Among the advantages of using a computer-based training program is the ease with which it can be implemented in school settings and the ease by which the difficulty of the tasks can be adapted to fit the child’s ability level. To test the effects of the training, children’s cognitive skills (EF and IQ) and their school achievement (math and language grades and abilities) were evaluated. The results revealed a significant improvement in cognitive skills, such as non-verbal IQ and inhibition, and better school performance in math and reading among the children who participated in the training compared to those children who did not. Most of the improvements were related to training on WM tasks. These findings confirmed the efficacy of a computer-based training that combined WM and mathematics activities as part of the school routines based on the training’s impact on children’s academic competences and cognitive skills.